Emerging drugs for the treatment of L-DOPA-induced dyskinesia: an update. (2nd April 2020) - AlShimemeri, Sohaila; Fox, Susan H; Visanji, Naomi P
ABSTRACT: Introduction: Prolonged treatment with L-3, 4-dihydroxyphenylalanine (L-DOPA) leads to the development of uncontrolled movements (L-DOPA-induced dyskinesias (LID)) in Parkinson's disease (PD). There is currently only a single approved drug for the treatment of LID, a long-acting preparation of the NMDA antagonist, amantadine, that has variable benefits and side-effects. Therefore, new treatments for LID remain an unmet in PD. Areas covered: We review the current strategies for the management of LID; the pathogenic mechanisms underlying the development of LID, which provides the rationale for clinical trials of novel targets for LID and provide a review of phase II/III trials for emerging drugs for LID, with either positive results, or ongoing studies, reported between January 2014 and December 2019. Expert opinion: There are several ongoing studies for agents that showed possible benefit at phase Ib/IIa for reducing LID. However, there are no new positive phase III double-blind randomized controlled clinical trials (DBRCT) for emerging treatments for LID. Generating better preclinical models, more precise recruitment tools and better outcome measures remain a priority. The pharmacology of drugs investigated for LID may be too selective; therefore, evaluating combinations of drugs is worthy of consideration as is the repurposing of existing drugs with multiple pharmacological targets.